2013
DOI: 10.1038/gim.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of epidermal growth factor receptor (EGFR) testing in the United States: a case study of T3 translational research

Abstract: Purpose We examined hospital use of the epidermal growth factor receptor (EGFR) assay for lung cancer patients. Our goal was to inform the development of a model to predict T3 translation of guideline-directed, molecular diagnostic tests. Methods This was a retrospective observational study. Using logistic regression, we analyzed the association between likelihood to order the EGFR assay and hospital’s institutional and regional characteristics. Results Significant institutional predictors included: Affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…Our previous research identified substantial underuse of genomic tests among hospitals located in nonmetropolitan counties that are distant from NCI cancer centers. 22 Medicaid coverage for the 21-gene test became available in 2007. However, a study conducted in New York City found that site of care significantly influenced utilization, and women treated at municipal hospitals were unlikely to get the 21-gene test even after Medicaid coverage should have ensured equal access.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research identified substantial underuse of genomic tests among hospitals located in nonmetropolitan counties that are distant from NCI cancer centers. 22 Medicaid coverage for the 21-gene test became available in 2007. However, a study conducted in New York City found that site of care significantly influenced utilization, and women treated at municipal hospitals were unlikely to get the 21-gene test even after Medicaid coverage should have ensured equal access.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with lung cancer molecular testing, 22 implementation of the 21-gene breast cancer test is widely distributed across the country. Although the percentage of patients tested ranged from 11.96 to 73.00%, this range is not particularly broad, especially given potential variations in age, comorbidities, stage, and incidence of ER+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicians in both Western and Asian hospitals tend to order EGFR first-line testing for never-smoking patients with NSCLC (40,41). In Singapore, all patients are tested for EGFR mutations regardless of smoking status.…”
Section: Discussionmentioning
confidence: 99%